Stability study of fluconazole applying validated bioassay and stability-indicating LC methods - Corrêa, Josilene Chaves Ruela [UNESP]; Reichman, Camila [UNESP]; Vianna-Soares, Cristina Duarte; Salgado, Hérida Regina Nunes [UNESP] (OMICS International, 2011)
Chemical degradation of drugs may result in altered therapeutic efficacy and even toxic effects. Therefore, understanding the factors that change the stability of pharmaceuticals and identifying ways to guarantee their stability are important. In this work stability-indicating Liquid Chromatographic (LC) and bioassay methods were validated and employed in the fluconazole stability studies. The correlation of sample results from both methods was evaluated. Fluconazole raw material stability was investigated in aqueous, acid (0.1 M HCl), alkaline (0.1 M NaOH) and oxidative (3% v/v H2O2) reflux for 6 hours, by LC method. Fluconazole capsules were exposed to UVC (254 nm, 66 and 180 days), climatic chamber (40°C, 75% RH, 90 days) and oven (60°C, 60 days), these samples were analyzed by LC and bioassay methods It was found that the drug is degraded (10% decrease) with arising of a possible degradation product in an oxidative medium and UVC exposure, in all the others conditions fluconazole remained chemically stable (higher than 98%) when analyzed by LC. However when the capsules stressed samples were evaluated through bioassay very low antifungal activity was found (about 30%). Fluconazole showed to be an unstable drug and it indicates that special care must be taken during the handling, storage and quality control using appropriated methods to analyze this therapeutic agent. This work suggests monitoring the fluconazole stability by bioassay and the stability-indicating LC methods.
Keywords: Fluconazole; Stability studies; Stability-indicating method; Liquid chromatography; Bioassay